Clustering Community Risk Behaviors for Non-Communicable Diseases in Indonesia: Based on Indonesian Health Survey Data - Hanif Pandu Suhito; Mahalul Azam; Dina Nur Anggraini Ningrum; Sholikun Sholikun (Media Kesehatan Masyarakat Indonesia, 2025)
Non-communicable Diseases (NCDs) such as hypertension, stroke, diabetes mellitus, and heart disease are major causes of morbidity and mortality in Indonesia. Community behaviors, including smoking, low physical activity, and unhealthy diets, significantly influence NCD incidence. To analyze associations between behavioral risk factors (daily smoking, physical inactivity, consumption of sugary foods and drinks, salty foods, fatty foods, soft drinks, and inadequate fruit intake) and the prevalence of NCDs, and to classify regions based on risk factors and disease prevalence. A cross-sectional study was conducted using secondary data from the 2023 Indonesian Health Survey (IHS), encompassing 345,000 households across 39 provinces. The Ministry of Health collected the data through standardized interviews and health examinations conducted by trained surveyors. Data analysis employed descriptive statistics, Pearson correlation, and K-Means Clustering. Daily smoking correlated positively with hypertension, stroke, and diabetes. Fatty food consumption showed strong positive associations with the same diseases (r = 0.45–0.48, p < 0.01). Soft drink consumption demonstrated a significant negative correlation, especially with stroke (r = -0.66, p < 0.001). Hypertension (7.2%) and stroke (7.1%) were more prevalent than diabetes (2.0%) and heart disease (0.76%). North Maluku showed the highest behavioral risks, Bali the lowest. DI Yogyakarta and DKI Jakarta had the highest NCD prevalence, while the Papua Mountains had the lowest. K-Means clustering grouped provinces into low, medium, and high-risk clusters. Community behaviors, particularly smoking and fatty food intake, significantly affect NCD prevalence. Public health programs should target smoking cessation, healthy diet promotion, and increased physical activity to reduce the NCD burden.